Improving the Quality of Educational Services through Strengthening the Competencies of Public Service Administrators - Hikmat; Bambang Mardi Sentosa; Andri Kurniawan; Aries Denta Putra; T.B Yudi Muhtadi (LPPM Akademi Teknik Adikarya, 2026)
The quality of educational services is a strategic determinant of institutional effectiveness, stakeholder satisfaction, and sustainable educational development. However, many educational institutions continue to face challenges related to inconsistent administrative performance, limited service competencies, inadequate responsiveness, and insufficient implementation of public service standards. This study aims to analyze how strengthening the competencies of public service administrators contributes to improving the quality of educational services. The research employed a qualitative approach using a descriptive case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving school administrators, education personnel, institutional leaders, teachers, and service users. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source triangulation, member checking, and prolonged engagement. The findings reveal that competency strengthening encompasses four interrelated dimensions: professional competence, communication competence, digital administrative competence, and public service ethics. The enhancement of these competencies contributes to faster administrative processes, greater service accuracy, improved transparency, stronger accountability, and more responsive interactions with stakeholders. Furthermore, institutional support through continuous professional development, digital transformation, leadership commitment, and standardized service procedures significantly reinforces competency development and organizational performance. The study concludes that strengthening the competencies of public service administrators is a fundamental strategy for enhancing educational service quality by promoting efficiency, effectiveness, and citizen-oriented service delivery. These findings provide practical implications for educational policymakers and institutional leaders in designing sustainable competency development programs that support excellent public service within educational institutions.